Pengaruh Psychological Contract, Job Stress, dan Workload terhadap Turnover Intention dengan Organizational Support sebagai Mediasi - Azmi, Gita Nurul; Yoga, Ika (https://jurnal.binamandiri.ac.id/, 2024)
Turnover intention, or employees' intention to leave their jobs, is a critical issue in human resource management. High turnover rates in a company can negatively impact the overall performance of the organization, both in terms of operational efficiency and the costs of recruitment and training to replace departing employees. This study examines the influence of psychological contract, job stress, and workload on turnover intention, with organizational support as a mediating variable, among employees of PT XYZ. The research uses a quantitative approach, collecting data through the distribution of questionnaires. The population of this study consists of 250 employees of PT XYZ, with a research sample of 100 respondents. The method of analysis employed is regression analysis. Based on the results, both psychological contract and job stress significantly affect turnover intention, either directly or through the mediating variable, organizational support. Meanwhile, workload does not have a significant effect on turnover intention through the organizational support variable.